Intermediaries and Capability Building in 'Emerging' Clusters. (August 2014) - Clarke, Ian; Ramirez, Matias
Increasing attention has begun to focus on the important role that organisations undertaking intermediary functions can play in supporting emerging clusters of small producers. In contrast to most studies of intermediaries that focus on governance and filling information gaps, in this paper we examine how the organisational skills of intermediaries evolve as firms in the cluster assume a broader range of practices. Through a purpose-built typology and a detailed case study, the argument is made not only that intermediaries act to facilitate the diffusion of knowledge but also that their scope of activities, extending into coordinating joint actions and new investment initiatives, places them at the centre of the network of organisations. This growing influence of intermediaries has implications for producer firms, especially in aspects such as inclusion of smaller producers and network formation.